Semen quality and reproductive health of young Czech men exposed to seasonal air pollution - Selevan, S G; Borkovec, L; Slott, V L; Zudová, Z; Rubes, J; Evenson, D P; Perreault, S D (Environmental health perspectives, 2000)
This study of male reproductive health in the Czech Republic resulted from community concern about potential adverse effects of air pollution. We compared young men (18 years of age) living in Teplice, a highly industrialized district with seasonally elevated levels of air pollution, to those from Prachatice, a rural district with relatively clean air. Surveys were scheduled for either late winter, after the season of higher air pollution, or at the end of summer, when pollution was low. Participation included a physical examination, donation of a semen sample, and completion of a questionnaire on health, personal habits, and exposure to solvents and metals through work or hobby. Analysis of data from 408 volunteers showed that the men from Teplice and Prachatice were similar in physical characteristics, personal habits, and work- or hobby-related exposures. Sixty-six percent (272) of these men donated a single semen sample for routine semen analysis, computer-aided sperm motion analysis, and sperm chromatin structure assay. The mean (median) sperm concentration and sperm count were 61. 2 (44.0) million/mL semen and 113.3 (81.5) million, respectively, and were not associated with district of residence or period of elevated air pollution. However, periods of elevated air pollution in Teplice were significantly associated with decrements in other semen measures including proportionately fewer motile sperm, proportionately fewer sperm with normal morphology or normal head shape, and proportionately more sperm with abnormal chromatin. These results suggest that young men may experience alterations in sperm quality after exposure to periods of elevated air pollution, without changes in sperm numbers.
Keywords: sperma; Reproduction; Humans; rozmnožování; městské obyvatelstvo; mužská infertilita; Sperm Count; průmysl; Sperm Motility; dospělí; Industry; chromatin; lidé; Air Pollution; Urban Population; Chromatin; Adult; venkovské obyvatelstvo; roční období; motilita spermií; Male; počet spermií; Adolescent; Seasons; Czech Republic; Infertility, Male; Semen; Rural Population; znečištění ovzduší; Česká republika; mužské pohlaví; mladiství